2013
DOI: 10.1073/pnas.1310145110
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging of the functional crosstalk between surface NMDA and dopamine D1 receptors

Abstract: Dopamine is a powerful modulator of glutamatergic neurotransmission and NMDA receptor-dependent synaptic plasticity. Although several intracellular cascades participating in this functional dialogue have been identified over the last few decades, the molecular crosstalk between surface dopamine and glutamate NMDA receptor (NMDAR) signaling still remains poorly understood. Using a combination of single-molecule detection imaging and electrophysiology in live hippocampal neurons, we demonstrate here that dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 31 publications
5
74
0
1
Order By: Relevance
“…[11][12][13] Using single-molecule approaches, differences in molecular behaviors have been uncovered among and within families of receptors including the excitatory glutamate alpha-amino-3-hydroxy-5-methylisoazol-4-propionate and N-methyl-D-aspartate (NMDA) receptors, inhibitory glycinergic and GABA A receptors, and modulatory dopamine receptors. 7,[14][15][16][17] Noteworthy, similar outcomes have been obtained when exploring the surface dynamics of neurotransmitter transporters in neurons and astrocytes (glutamate transporter GLT1 and dopamine transporter). 18,19 Among the glutamatergic receptors, NMDA receptors (NMDAR) have attracted much attention since they play a key role in synaptic plasticity processes, network maturation, cognitive functions, and because impairments in NMDAR signaling have been associated with severe neuropsychiatric conditions.…”
Section: Introductionmentioning
confidence: 56%
“…[11][12][13] Using single-molecule approaches, differences in molecular behaviors have been uncovered among and within families of receptors including the excitatory glutamate alpha-amino-3-hydroxy-5-methylisoazol-4-propionate and N-methyl-D-aspartate (NMDA) receptors, inhibitory glycinergic and GABA A receptors, and modulatory dopamine receptors. 7,[14][15][16][17] Noteworthy, similar outcomes have been obtained when exploring the surface dynamics of neurotransmitter transporters in neurons and astrocytes (glutamate transporter GLT1 and dopamine transporter). 18,19 Among the glutamatergic receptors, NMDA receptors (NMDAR) have attracted much attention since they play a key role in synaptic plasticity processes, network maturation, cognitive functions, and because impairments in NMDAR signaling have been associated with severe neuropsychiatric conditions.…”
Section: Introductionmentioning
confidence: 56%
“…Previously, our studies showed that stimulation of striatal slices with a D1 agonist or NMDA led to dephosphorylation of WAVE1 at Ser310, Ser397, and Ser441, indicating neuronal activity-mediated stimulation of WAVE1 (4, 7). We anticipated that WAVE1 would be dephosphorylated in response to cocaine administration in vivo, because cocaine increases synaptic levels of dopamine, and activation of D1 is known to increase NMDA-receptor-mediated signaling (13,28,29). However, there was no significant change in phosphorylation, or of the total protein level, of WAVE1 in the striatum in response to acute injection of cocaine (45 min after 15 mg/kg) or chronic injection of cocaine (15 mg/kg daily for 14 d; 45 min after the last injection).…”
Section: Resultsmentioning
confidence: 99%
“…activation of NMDARs recruits D1Rs to the synaptic membrane retaining D1Rs in close proximity to NMDARs in the membrane [82,72]. In addition, it was reported that D1Rs and NMDARs are in direct interaction in the hippocampus [57,55,56]. On the other hand, coexpression of GluN2 with D1 is necessary to recruit the D1-NMDAR complex to the synaptic membrane [9].…”
Section: Discussionmentioning
confidence: 99%